On the problem of rare earth element distribution in human organs and tissues (by the example of the inhabitants of Tomsk Region); Trace Elements in Human: new Perspectives - Ignatova T. N.; Baranovskaya N. V. Nataliya Vladimirovna; Rikhvanov L. P. Leonid Petrovich; Matveenko I. A. (2009, 2009)
В фонде НТБ ТПУ отсутствует